Development of Teaching Materials for Learning Clocks and Evaluation in a Multiple Baseline Design (Pedagogical Horizons, 2023)
Reading the clock and an advanced understanding of time are, on the one hand, competencies that are highly relevant for later participation in society, and on the other hand, they pose a great challenge to many learners. From the perspective of teachers, there is also a great need for didactic concepts and materials for the development of this learning area in inclusive learning settings. In this project, teaching materials for learning in the learning area of time were developed. These materials were subsequently tested for their effectiveness and applicability within a multiple baseline design. Five girls and one adult female participated in the evaluation study. Four of the six participants live with a so-called cognitive impairment. Sixty test items were developed to measure learning progress. All participants showed improvements, although the effect sizes varied. Overall, the support with the developed materials led to an improvement of the competences in clock reading and time perception. Due to the modularization, the material can be used in any way and is also suitable for different learning levels. The entire learning material is made available under an open license as an Open Educational Resource.
Keywords: Clock Learning; Time; Teaching Materials; Single Case Research Design; Multiple Baseline Design; Open Educational Resources